2020
DOI: 10.1017/jwe.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Buyer-Seller Relations in Norwegian Wine Imports

Abstract: As for all traded products, aggregated wine imports build on numerous trades at the firm level. To ensure consumers access to a variety of wines with different qualities, importers need to connect to different wine exporters. Some of these relationships will last for a long time, while the duration of others may be short. In this article, we employ transaction-level data to analyze the duration of trade relationships in wine imports to Norway from 2004 to 2014. We find that most relationships are short-lived, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Other authors like Menon et al (1996) studied the importance of communication quality of the business success relationships, which, translated to our theme, will impact economic performance. The long-term relationship and importer involvement were also verified as crucial to the business success by studies like Landazuri-Tveteraas et al (2021).…”
Section: Discussionmentioning
confidence: 88%
“…Other authors like Menon et al (1996) studied the importance of communication quality of the business success relationships, which, translated to our theme, will impact economic performance. The long-term relationship and importer involvement were also verified as crucial to the business success by studies like Landazuri-Tveteraas et al (2021).…”
Section: Discussionmentioning
confidence: 88%
“…Better access to microdata has made it possible for researchers to suggest different approaches as to how total sales at the firm level can be attributed to different margins of trade. Some relevant examples for trade in general are Bernard et al (2007) , Lawless (2010) , Hornok and Koren (2015) , Asche et al (2021b) , and Landazuri-Tveteraas et al, 2021a , Landazuri-Tveteraas et al, 2021b . Specific to seafood, Straume et al (2020b) investigates if trade margins for aquaculture products differ from trade margins in wild seafood products beyond just total export value.…”
Section: Margins Of Tradementioning
confidence: 99%
“…The fact that the price effects have different signs is notable, as a number of studies have reported that the salmon market is highly integrated ( Landazuri-Tveteraas et al, 2021a , Landazuri-Tveteraas et al, 2021b ; Salazar and Dresdner, 2021 ). However, Landazuri-Tveteras et al, (2018) show that the degree of price transmission varies significantly between product forms, and, as such, this result highlights the fact that the short-run dynamics vary by product form.…”
Section: Trade Margins and Lockdown Stringencymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in practice, the cooperative relationship between contract farmers and enterprises, especially their long-term cooperative relationships, is very unstable and even leads to frequent conflicts. In recent years, relationship governance has been widely used in studying the stability of relations [14][15][16]. Relationship governance is a governance mechanism that uses interpersonal relationships and emotional means to ensure the smooth implementation of contracts.…”
Section: Introductionmentioning
confidence: 99%